Tectono-metamorphic evolution of the continental units along the edge between Alpine and Hercynian Corsica Constraints for the exhumation models in the continental collision setting - Di Rosa, Maria (Premio Tesi di Dottorato, 2021)
In this work the central area of Corsica island was studied in order to reconstruct the tectono-metamorphic history of the continental and oceanic high pressure units that occupy the structurally deeper levels of the tectonic stacking of Alpine Corsica and their stratigraphic and structural relationship with the European margin (Hercynian Corsica). The study includes the geological mapping, the mesoscale and microscale structural analysis, the acquisition of chemical analyzes and micromaps with the microprobe, thermobarometric estimation through specific methodologies for metapelites, U-Th-Pb dating of zircons and allanites. The results obtained allows to reconstruct the geodynamic model of this sector of the Alpine belt from the Permian to the Burdigalian.